Human dental pulp stem cell monolayer and spheroid therapy after spinal motor root avulsion in adult rats - Paes, Sabrina Moreira; Castro, Mateus Vidigal de; Barbosa, Rafael Maza; Politti Cartarozzi, Luciana; Coser, Lilian de Oliveira; Kempe, Paula Regina Gelinski; Decarli, Monize Caiado; Moraes, Ângela Maria; Barraviera, Benedito [UNESP]; Ferreira Júnior, Rui Seabra [UNESP]; Oliveira, Alexandre Leite Rodrigues de (Elsevier, 2023)
Spinal cord injuries result in severe neurological deficits and neuronal loss, with poor functional recovery. Mesenchymal stem cells have shown promising results; therefore the present objective of this work was to compare motor recovery after treatment with human dental pulp stem cells (hDPSC) cultivated in monolayer (2D) or as spheroids (3D), following avulsion and reimplantation of spinal motor roots in adult rats. Thus, 72 adult female Lewis rats were divided into 4 groups: avulsion (AV); avulsion followed by reimplantation (AR); avulsion associated with reimplant and 2D cell therapy (AR + 2D), and avulsion associated with reimplant and 3D cell therapy (AR + 3D). The application of the cells in 2D and 3D was performed by microsurgery, with subsequent functional assessment using a walking track test (Catwalk system), immunohistochemistry, neuronal survival, and qRT-PCR in 1-, 4-, and 12-weeks post-injury. The animals in the AR + 2D and AR + 3D groups showed the highest neuronal survival rates, and immunofluorescence revealed downregulation of GFAP, and Iba-1, with preservation of synaptophysin, indicating a reduction in glial reactivity, combined with the maintenance of pre-synaptic inputs. There was an increase in anti-inflammatory (IL-4, TGFβ) and a reduction of pro-inflammatory factors (IL-6, TNFα) in animals treated with reimplantation and hDPSC. As for the functional recovery, in all analyzed parameters, the AR + 2D group performed better and was superior to the avulsion alone. Overall, our results indicate that the 2D and 3D cell therapy approaches provide successful immunomodulation and motor recovery, consistent with advanced therapies after spinal cord injury.
Keywords: Cell therapy; Dental pulp; Spheroid; Spinal cord injury